Straddling Two Geographic Regions: the Impact of Place of Origin and Destination on Return Migration Intentions in China. Issue 3 (12th April 2012) - Piotrowski, Martin; Tong, Yuying
ABSTRACT: Using data from a destination sample of labour migrants ( N  = 1, 100) from China's Pearl River Delta, we develop and empirically evaluate a model of return migration intentions over multiple time horizons. We argue that return migration involves a complex decision‐making process whereby migrants, who are situated in a trans‐region social space spanning migration origin and destination areas, are influenced by economic and non‐economic factors in these distinct settings. Migrants weight the value of factors in both geographic regions and have shifting ideas about their future settlement. Results show that both economic and non‐economic factors operate in two distinct geographic spaces. Economic factors related to destination earning ability operate mainly in short time horizons. Also, migrants are sensitive to the economic situation of the origin household. Non‐economic factors related to child's location at origin and the migrants' living situation at destination are also significant, especially over long time horizons. Copyright © 2012 John Wiley & Sons, Ltd.